Size-segregated characteristics of bioaerosols during foggy and non-foggy days of winter, meteorological implications, and health risk assessment - Vishwakarma Y.K.; Ram K.; Gogoi M.M.; Banerjee T.; Singh R.S. (My University, 2025)
Fog is a common atmospheric event in northern India. Frequently, dense and prolonged fog envelops the entire Indo-Gangetic Plain (IGP), especially in the winter season. During winter, conducive atmospheric conditions also facilitate the accumulation of airborne particulates near the earth surface, significantly reducing atmospheric visibility in the presence of water vapour and gases. Besides, fog formation can also change the characteristics of the biological component of the air (bioaerosols). The Anderson six-stage bioaerosol cascade impactor was therefore used to collect bioaerosols during winter-specific foggy and non-foggy days to assess how fog formation affects the loading and characteristic of bioaerosols. It has been found that the concentration of bioaerosols increases during foggy days (2223 ± 553 CFU m−3) compared to non-foggy days (days including both before and after fog; 1478 ± 490 CFU m−3). Nearly, a 50% rise in the total culturable microbe concentration was noted during foggy days as compared to non-foggy days in an urban habitat over the central IGP. Approximately 46% and 55% increase in bacterial and fungal bioaerosol concentration, respectively, was found to be associated with foggy days. The size of bioaerosols also varied with the change in atmospheric conditions. During foggy days, bacterial and fungal concentration increased in the coarse size fraction (4.7-7.0 μm) compared to fine (0.65-7.0 μm) particles. The presence of bacteria such as Bacillus; Enterobacter; Cocci and fungi such as Aspergillus, Cladosporium and Penicillium were found during foggy days. The measured concentration of bioaerosols did not exhibit strong association with meteorological variables and other atmospheric co-pollutants. Health risk assessment of the exposure to bioaerosols revealed strong possibility to cause adverse human health effects in the exposed population. © 2024 RSC.